Issues in introducing resource brokerage functionality in B3G composite radio environments. - Demestichas, P. (IEEE Wireless communications)
This article identifies and discusses problems that should be addressed for introducing resource brokerage functionality in beyond-third-generation wireless environments. Resource brokerage is a capability required by the B3G concept. It enables cooperation between NPs in handling new service area conditions that originate in a network of the B3G infrastructure. The article starts from a business case that justifies the need for RB functionality. Its integration in management systems for composite radio environments (MS-CRE) is also presented. Subsequently, there is a presentation of the RB process interfaces, as well as the approach taken to decompose the overall process into smaller problems. Finally, there is a description of the individual tasks: selection of QoS levels, demand volume, and prices.